Excitable networks controlling cell migration during development and disease. (April 2020) - Li, Xiaoguang; Miao, Yuchuan; Pal, Dhiman Sankar; Devreotes, Peter N.
ABSTRACT: The directed movements of individual, groups, or sheets of cells at specific times in particular locations bring about form and complexity to developing organisms. Cells move by extending protrusions, such as macropinosomes, pseudopods, lamellipods, filopods, or blebs. Although many of the cytoskeletal components within these structures are known, less is known about the mechanisms that determine their location, number, and characteristics. Recent evidence suggests that control may be exerted by a signal transduction excitable network whose components and activities, including Ras, PI3K, TorC2, and phosphoinositides, self-organize on the plasma membrane and propagate in waves. The waves drive the various types of protrusions, which in turn, determine the modes of cell migration. Acute perturbations at specific points in the network produce abrupt shifts in protrusion type, including transitions from pseudopods to filopods or lamellipods. These observations have also contributed to a delineation of the signal transduction network, including candidate fast positive and delayed negative feedback loops. The network contains many oncogenes and tumor suppressors, and other molecules which have recently been implicated in developmental and metabolic abnormalities. Thus, the concept of signal transduction network excitability in cell migration can be used to understand disease states and morphological changes occurring in development.